A multitasking PC based robotic ARM manipulator control system in RT-Linux environment - Md. Adnan Al Moshi; Islam, Md. Eftakhairul; Cynthia, Salwa Salam (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.